What Is Wrong with Eating Pets? Wittgensteinian Animal Ethics and Its Need for Empirical Data - Erich Linder; Herwig Grimm (Animals, 2023)
Wittgensteinian approaches to animal ethics highlight the significance of practical concepts like ‘pet’, ‘patient’, or ‘companion’ in shaping our understanding of how we should treat non-human animals. For Wittgensteinian animal ethicists, moral principles alone cannot ground moral judgments about our treatment of animals. Instead, moral reflection must begin with acknowledging the practical relations that tie us to animals. Morality emerges within practical contexts. Context-dependent conceptualisations form our moral outlook. In this paper, we argue that Wittgensteinians should, for methodological reasons, pay more attention to empirical data from the social sciences such as sociology, psychology or anthropology. Such data can ground Wittgensteinians’ moral inquiry and thereby render their topical views more dialectically robust.